2016
DOI: 10.1093/humrep/dew061
|View full text |Cite
|
Sign up to set email alerts
|

Sperm telomere length as a parameter of sperm quality in normozoospermic men

Abstract: No external funding was either sought or obtained for this study. There are no conflicts of interest to be declared.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
65
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 44 publications
14
65
5
Order By: Relevance
“…The positive correlations between the STL and the total sperm count and progressive motility as well as the negative correlations between the STL and the DFI and ROS content are consistent with a previous study that indicated that the STL is associated with most of the important standard semen parameters and sperm quality151743. And our recent study found that the semen samples of overweight/obese males had a shorter STL and increased DNA fragmentation and ROS levels44.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The positive correlations between the STL and the total sperm count and progressive motility as well as the negative correlations between the STL and the DFI and ROS content are consistent with a previous study that indicated that the STL is associated with most of the important standard semen parameters and sperm quality151743. And our recent study found that the semen samples of overweight/obese males had a shorter STL and increased DNA fragmentation and ROS levels44.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, our previous study demonstrated a positive correlation between the telomere length and embryo quality in the early stages of development15, and another study reported that spermatozoa telomeres determine the telomere length of early embryos and offspring16. A recent report also showed that the STL could be used as a new parameter in diagnosing infertility in males17. Therefore, the selection of functional sperm with less DNA damage and longer telomeres should be prerequisites for achieving optimal outcomes for ART.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Any age-specific process that affects sperm and egg TL will influence the pool from which gamete telomeres can be chosen and will consequently affect offspring TL-an age effect on chick TL. Age-related telomere shortening (Hall et al, 2004;Haussmann & Marchetto, 2010;Haussmann et al, 2003), telomerase activity in the germ line of adult birds (Haussmann, Winkler, Huntington, Nisbet, & Vleck, 2004;Haussmann et al, 2007), a reduction in sperm quality with age (Ferlin et al, 2013;Rocca et al, 2016;Waeleghem, Clercq, Vermeulen, Schoonjans, & Comhaire, 1996), TL-based selective stem cell turnover (Kimura et al, 2008), and stochastic processes during sperm maturation that increase variability in sperm TL as the individual ages (De Meyer & Eisenberg, 2015) could all increase the variability of TL in the gametes from which the zygote is formed (De Meyer & Eisenberg, 2015). Smallsample random sampling from this distribution could produce many possible patterns of parental age effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, shorter telomeres have been observed in infertile than fertile males [27] . Currently, a survey has demonstrated that SLT is connected with the motility and vitality of sperm, as well as sperm DNA fragmentation [28] . Another investigation on adult male Brown Norway rats has indicated an association between chemotherapy treatment and the reduction of the telomere length in spermatocytes [29] .…”
Section: Introductionmentioning
confidence: 99%